Transition metal oxide based resistive RAM for high density non-vilatile memory - Tran, Xuan Anh (2013)
Nonvolatile memory technology (NVM) is one of the key driving factors for information storage development. With memory technology aggressively migrating into the sub-10 nm nano-scale regime, the traditional nonvolatile FLASH memory is facing challenging issues such as lithography, coupling ratio, cross-talk between cells and short channel effect. It is essential to identify replacement emerging memory devices as potential alternatives for next generation of memory technology. Recently, Resistive Random Access Memory (RRAM) has emerged as one of promising candidates succeeding the conventional FLASH memory due to its low cost, simple structure, low power dissipation, high endurance and compatibility with CMOS technology. Recently, transition metal oxide (TMO) materials have attracted great attention as switching materials largely because of their simple composition and outstanding performance. A unique high performance unipolar RRAM based on HfOx and AlOy dielectrics and Ni electrode is investigated in this work. By using highly doped Si as bottom electrode, the memory cell makes it feasible to exploit a vertical Si-diode as a selector for RRAM crossbar architecture, highly suitable for low-cost three-dimensional (3D) integration. To improve the performance of RRAM devices, bi-layer HfOx/AlOy dielectric structures are studied. With bi-layer structures and the doping effect, the tight distribution of switching parameters could be greatly enhanced. Self-rectifying voltage-current characteristics of RRAM devices are encouraging to increase the array size without integrating selector (e.g. diode, transistor, etc.), so that higher integration density could be achieved for the cross-bar architecture. RRAM device with forming-free, unipolar switching, and self-selection for cross-point architecture is demonstrated successfully. With self-rectifying characteristic and high forward current density, the sneak current path in the conventional cross-bar architecture is effectively eliminated. The fabricated devices show great potential application for nano-scaled memory technology. Being possible in cross-bar architecture, the memory cell can be scaled to dimensions, the best possible scaling so far in memory. Owning to superior bipolar resistive switching characteristic, the bipolar RRAM with cross-bar architecture has received widespread attentions. A CMOS friendly and low fabrication cost RRAM device with bipolar switching characteristic, ultra-low current, and self-selection is exploited for RRAM cross-point array application in this work. Vertical RRAM (VRRAM) cross-point structure with vertical Si-nanowire MOSFET is proposed to achieve ultra-high density integration and low fabrication cost. VRRAM cross-point structure could be fabricated and operated correctly based on the fabricated device. By stacking the cross-point arrays in n layers, an effective cell size of 4F2/n could be achieved.